How to be a Tudor : a dawn-to-dusk guide to Tudor life - Goodman, Ruth, 1963- (Liveright Publishing Corporation, 2016)
"Drawing on her own adventures living in re-created Tudor conditions, Goodman serves as our ... guide to sixteenth-century living. Proceeding from daybreak to bedtime, this ... illustrative work celebrates the ordinary lives of those who labored through the era. From sounding the hue and cry to alert a village to danger to malting grain for homemade ale, from the gruesome sport of bear-baiting cuckolding and cross-dressing--the madcap habits and revealing intimacies of life in the time of Shakespeare are ... rendered for the insatiably curious"--Amazon.com.